Ex-ante Evaluation of the Impact of Increases in Minimum Wages on Labor Market Outcomes in Kosovo - Robayo-Abril, Monica; Terskaya, Anastasia; Brodmann, Stefanie (World Bank, Washington, DC, 2020)
This paper uses microsimulation techniques to quantify the potential ex-ante impacts of several minimum wage increases on labor market outcomes in Kosovo. The results show that the overall impacts of a minimum wage increase in the baseline scenario are likely to be modest, although the impacts for some groups may be stronger. In the most extreme scenario, an increase to 250 euros per month, the simulated unemployment rate increases by 0.4 percentage point in the short term and about 0.6 percentage point in the long term. The youth unemployment rate (ages 15-24) is anticipated to increase by up to 1.1 percentage points in this scenario, a relatively large increase considering the already high levels of unemployment among this group. Similarly, unemployment among the unskilled (with primary school or less) is simulated to increase by 0.6 percentage point in the short term and up to 0.8 percentage point in the long term. The paper finds that, even if raising the minimum wage is long overdue, due to decreasing nominal wages in real terms, policy needs to strike a fine balance between protecting workers and ensuring that employment effects are not too large.